Full-field analysis of epicardial strain in an in vitro porcine heart platform. (March 2019) - Ferraiuoli, Paolo; Kappler, Benjamin; van Tuijl, Sjoerd; Stijnen, Marco; de Mol, Bas A.J.M.; Fenner, John W.; Narracott, Andrew J.
Abstract: The quantitative assessment of cardiac strain is increasingly performed to provide valuable insights on heart function. Currently, the most frequently used technique in the clinic is ultrasound-based speckle tracking echocardiography (STE). However, verification and validation of this modality are still under investigation and further reference measurements are required to support this activity. The aim of this work was to enable these reference measurements using a dynamic beating heart simulator to ensure reproducible, controlled, and realistic haemodynamic conditions and to validate the reliability of optical-based three-dimensional digital image correlation (3D-DIC) for a dynamic full-field analysis of epicardial strain. Specifically, performance assessment of 3D-DIC was carried out by evaluating the accuracy and repeatability of the strain measurements across multiple cardiac cycles in a single heart and between five hearts. Moreover, the ability of this optical method to differentiate strain variations when different haemodynamic conditions were imposed in the same heart was examined. Strain measurements were successfully accomplished in a region of the lateral left ventricle surface. Results were highly repeatable over heartbeats and across hearts (intraclass correlation coefficient = 0.99), whilst strain magnitude was significantly different between hearts, due to change in anatomy and wall thickness. Within an individual heart, strain variations between different haemodynamic scenarios were greater than the estimated error of the measurement technique. This study demonstrated the feasibility of applying 3D-DIC in a dynamic passive heart simulator. Most importantly, non-contact measurements were obtained at a high spatial resolution ( ~ 1.5 mm) allowing resolution of local variation of strain on the epicardial surface during ventricular filling. The experimental framework developed in this paper provides detailed measurement of cardiac strains under controlled conditions, as a reference for validation of clinical cardiac strain imaging modalities. Graphical abstract: fx1 Highlights: An experimental protocol to analyse full-field epicardial strain in vitro is presented. Accuracy and repeatability of digital image correlation (DIC) are assessed across multiple hearts and cardiac cycles. Surface strain fields on the heart are reported at a higher resolution than those obtained with conventional optical methods. In this framework, DIC can serve as a reference for ultrasound-based﻿ cardiac strain analysis.